Analysis of Capital Structure, Liquidity and Firm Size on Financial Performance and Firm Value in Technological Sector - Wijaya, Evelyn; Wijaya, Fuma; Chandra, Stefani; Musa, Sulaiman (Research in Accounting Journal (RAJ), 2025)
Indonesia’s technology industry is experiencing strong growth prospects, supported by solid fundamentals and the rapid expansion of fintech infrastructure. The digital economy’s Gross Merchandise Value (GMV) is projected to grow at a compound annual growth rate (CAGR) of 14% during 2024–2030, driven by continuous innovation in e-commerce, increasing digital adoption through QRIS, and the strengthening of technology-based financial ecosystems. This study aims to examine the effect of capital structure, liquidity, and firm size on financial performance and firm value in the technology sector. The research employs secondary data collected through a purposive sampling technique, resulting in a sample of 15 companies. Data were analyzed using descriptive statistics and structural equation modeling (SEM) with SmartPLS. The results indicate that (1) capital structure, liquidity, and firm size have a negative and insignificant effect on financial performance, and (2) capital structure, liquidity, firm size, and financial performance have a positive but insignificant effect on firm value. These findings suggest that internal financial characteristics have not yet demonstrated a statistically significant role in determining financial performance and firm value within Indonesia’s technology sector.